Osteopontin as a tumor marker in ovarian cancer - Shikha Rani; Alka Sehgal; Jasbinder Kaur; Dilpreet Kaur Pandher; Rajpal Singh Punia (Wolters Kluwer Medknow Publications, 2022)
Introduction: Ovarian cancer is associated with high morbidity and mortality. This is due to the nonspecific symptoms and no effective screening methods. Currently, carbohydrate antigen-125 (CA125) is used as a tumor biomarker for the diagnosis of ovarian cancer, but it has its own limitations. Hence, there is a need for other tumor biomarkers for the diagnosis of ovarian cancer. Objective of the study was to evaluate the diagnostic test characteristics of plasma osteopontin (OPN) in detecting ovarian malignancy and comparing its performance with CA125. Materials and Methods: This is a prospective cross-sectional diagnostic test evaluation. Women with adnexal mass detected by clinical or radiological examination were enrolled as suspected cases. Women who presented with other gynecological conditions were enrolled as controls. OPN and CA125 levels were measured in all enrolled subjects. Results: Among 106 women enrolled, 26 were ovarian cancer, 31 had benign ovarian masses, and 49 were controls. Median plasma CA125 levels were higher in subjects with ovarian cancer (298 U/ml; interquartile range [IQR]: 84-1082 U/ml vs. 37.5U/ml; IQR: 17.6-82.9U/ml; P < 0.001). CA125 sensitivity, specificity, positive, and negative likelihood ratios were 88.5%, 61.3%, 2.10, and 0.19, respectively. Median plasma OPN levels were higher in subjects with ovarian cancer (63.1 ng/ml; IQR: 39.3-137 ng/ml vs. 27 ng/ml; IQR: 20-52 ng/ml; P = 0.001). Sensitivity, specificity, positive, and negative likelihood ratios of OPN were 50%, 87%, 2.58, and 0.62, respectively. Conclusion: OPN levels were higher in ovarian cancer than in the benign ovarian mass and had better specificity than CA125. OPN can better differentiate between benign and malignant ovarian mass as compared to CA125.